PENGARUH TEKNIK PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN MOTIVASI BELAJAR SISWA KELAS IV DI MI NAHDLATUL ULAMA BULULAWANG - Firdausi, Rofiqoh (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
The 2013 curriculum emphasizes students to think integratively. Effective learning techniques are needed to provide a complete understanding of the concept. The effective learning techniques is the Numbered Head Together (NHT) in increasing concept understanding and learning motivation on the sub-themes of various energy sources.This research uses a quantitative approach, with a quasi experimental. The population were fourth grade students at MINU Bululawang, and the samples were students in grade IV B and IV E. This research uses pre-test to measure students' initial abilities. The post-test activity was carried out with the t-test. To measure motivation through the results of a questionnaire using the validity test and reliability test. The results of this research consisted of: 1) the level of understanding of the sub-theme concepts of various energy sources for fourth grade students who learned using NHT was better than conventional learning techniques of 0.429 (results from t-test) and 2) the level of motivation to learn various sub-themes the kinds of energy sources for fourth grade students with NHT were 0.733 better than conventional learning techniques which were 0.704. Of course this is greater than r table = 0.361.